Host GRXC6 restricts Tomato yellow leaf curl virus infection by inhibiting the nuclear export of the V2 protein - Zhao, Wenhao; Zhou, Yijun; Zhou, Xueping; Wang, Xiaofeng; Ji, Yinghua (PLoS pathogens, 2021)
Geminiviruses cause serious symptoms and devastating losses in crop plants. With a circular, single-stranded DNA genome, geminiviruses multiply their genomic DNA in the nucleus, requiring the nuclear shuttling of viral proteins and viral genomic DNAs. Many host factors, acting as proviral or antiviral factors, play key roles in geminivirus infections. Here, we report the roles of a tomato glutaredoxin (GRX), SlGRXC6, in the infection of Tomato yellow leaf curl virus (TYLCV), a single-component geminivirus. The V2 protein of TYLCV specifically and preferentially interacts with SlGRXC6 among the 55-member tomato GRX family that are broadly involved in oxidative stress responses, plant development, and pathogen responses. We show that overexpressed SlGRXC6 increases the nuclear accumulation of V2 by inhibiting its nuclear export and, in turn, inhibits trafficking of the V1 protein and viral genomic DNA. Conversely, the silenced expression of SlGRXC6 leads to an enhanced susceptibility to TYLCV. SlGRXC6 is also involved in symptom development as we observed a positive correlation where overexpression of SlGRXC6 promotes while knockdown of SlGRXC6 expression inhibits plant growth. We further showed that SlGRXC6 works with SlNTRC80, a tomato NADPH-dependent thioredoxin reductase, to regulate plant growth. V2 didn’t interact with SlNTRC80 but competed with SlNTR80 for binding to SlGRXC6, suggesting that the V2-disrupted SlGRXC6-SlNTRC80 interaction is partially responsible for the virus-caused symptoms. These results suggest that SlGRXC6 functions as a host restriction factor that inhibits the nuclear trafficking of viral components and point out a new way to control TYLCV infection by targeting the V2-SlGRXC6 interaction.